Pengaruh Disposisi Matematis Terhadap Kemampuan Berpikir Kritis Pada Siswa SMP - Siti Sa'adah; Luvy Sylviana Zanthy (Departement of Mathematics Education, 2019)
This study aims to analyze examine in depth about the students’ mathematical critical thinking ability influenced by mathematics disposition . The study was designed in the form of experiments using linear regression . The population in this research is junior high school student in Bandung and the sample as many as 36 people determined by purposive sampling technique in one of junior high school in Bandung. The instrumen in this research is the test of mathematical critical thinking ability as much as 5 items and the scale of students’ mathematics disposition as much as 30 scale statement . Based on the result and discussion, it is concluded that the students’ mathematical critical thinking ability influenced positively by mathematics disposition equal 82,5%, while 17,5% influenced by factors others than student mathematics disposition